2022
DOI: 10.3762/bjnano.13.126
|View full text |Cite
|
Sign up to set email alerts
|

Non-stoichiometric magnetite as catalyst for the photocatalytic degradation of phenol and 2,6-dibromo-4-methylphenol – a new approach in water treatment

Abstract: Phenol and 2,6-dibromo-4-methylphenol (DBMP) were removed from aqueous solutions by ozonolysis and photocatalysis. The properties and structural features of the catalysts and the organic compounds are discussed, as well as their influence on the degradation reaction rates. The degradation efficiency in photocatalytic processes was higher for DBMP (98%) than for phenol (approximately 50%). This proves the high efficiency of magnetite in the photocatalytic degradation of halogenated aromatic pollutants. The part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The average crystallite sizes of F1 and F2 catalyst are 46 and 28 nm, respectively. The lengths of the edges of the magnetite unit cells measured for F1 and F2 were 8.3845 Å and 8.3595 Å, respectively [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The average crystallite sizes of F1 and F2 catalyst are 46 and 28 nm, respectively. The lengths of the edges of the magnetite unit cells measured for F1 and F2 were 8.3845 Å and 8.3595 Å, respectively [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using these data and the unit cell edge length values obtained from XRD measurements of the materials F1 and F2 (8.3845 and 8.3595 Å, respectively) the x values were determined. The studied catalysts were non-stoichiometric magnetites with the x-value equal to 0.4094 and 0.1828 for F1 and F2, respectively [ 30 ]. Therefore, F1 exhibits the properties of a conductor (E bg = 0.11 eV, Figure S1 ), while F2 is a semiconductor (E bg = 1.75 eV).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers con rmed that the e ciency and performance of photocatalytic decomposition model is strongly depended to UV-light strength and so it is made the low performance for O 3 molecules removing in normal temperature [15,16]. Researchers indicated that the catalytic decomposition model has high performance, stability and durability and this model can be considered as effective method for O 3 molecules removing in engineering application [17,18].…”
Section: Introductionmentioning
confidence: 99%